Apatite (U–Th)/He thermochronology and Re–Os ages in the Altar region, Central Andes (31°30′S), Main Cordillera of San Juan, Argentina: implications of rapid exhumation in the porphyry Cu (Au) metal endowment and regional tectonics - Maydagán, Laura (2020)
Altar is a large porphyry Cu (Au) deposit located in the Main Cordillera of Argentina, 20 km to the north of the giant Los Pelambres–El Pachón porphyry copper cluster, at the southern portion of the Pampean flat-slab segment of the Andes. Although this region hosts telescoped porphyry-epithermal deposits, the precise temporal relationship between porphyry emplacement, mineralization, cooling, and regional orogenic uplift are still poorly understood. New Re–Os molybdenite ages indicate that Altar orebodies are associated with two magmatic hydrothermal centers: Altar East (11.16 ± 0.06 Ma) and Altar Central (10.38 ± 0.05 Ma) formed at temporally distinct periods. New (U–Th)/He ages from the Early Permian and Late Eocene plutons, and the Middle Miocene subvolcanic stocks associated with Cu–Au mineralization of the Altar region reflect a rapid cooling pulse during the Middle Miocene (15.02 to 10.66 Ma) coeval with a major phase of tectonic shortening and regional uplift. The main pulse of rapid cooling and related tectonic uplift in the Altar region was synchronous with the formation of the hydrothermal systems and resulted in an increased focused metal endowment (Au–Cu grades) due to the telescoping of epithermal mineralization over the rapidly uplifted porphyry system. This 11–10 Ma tectonically triggered exhumation event coincides with the collision of the E-trending segment of the Juan Fernández Ridge with the Peru–Chile trench, at this latitude. Collision and ensuing ridge subduction may have driven a localized pulse of rapid cooling and exhumation of the Main Cordillera that has not been well documented to the north or south of the Altar–Los Pelambres region.